Case Report and literature review: Delayed diagnosis of ARCL1B due to a newly reported homozygous mutation c.464A>C p. (Tyr155Ser) in the EFEMP2 gene - Ouyang, Lixue; Yang, Fan; Duan, Hongyu; Wang, Chuan (Frontiers in Genetics, 2024)
BackgroundAutosomal recessive cutis laxa type 1B (ARCL1B) is an extremely rare disease characterized by severe systemic connective tissue abnormalities, including cutis laxa, aneurysm and fragility of blood vessels, birth fractures and emphysema. The severity of this disease ranges from perinatal death to manifestations compatible with survival. To date, no cases have been reported in the Chinese population. Due to its rarity, the disease is susceptible to misdiagnosis or missed diagnosis by clinicians. By presenting this case and reviewing the relevant literature, the aim is to enhance clinicians’ awareness and vigilance in diagnosing this disease.Case presentationWe report a 7-month-old Chinese male infant who initially presented with severe respiratory infection, respiratory failure, and heart failure, and was misdiagnosed with Takayasu arteritis. Despite treatment, his condition did not improve. Due to the features of vascular malformations, developmental delay, and early onset of the disease, whole exome sequencing (WES) was performed, results revealed a homozygous mutation c.464A>C in exon 5 on the EFEMP2 gene p. (Tyr155Ser) that had never been reported before. Molecular protein prediction results suggest that this mutation site exhibits a high probability of pathogenicity. Combining the clinical manifestations, the results of cardiac color ultrasound and cardiac great vessels angiography, and the WES results, the patient was finally diagnosed with ARCL1B. Given the absence of established guidelines for the clinical manifestation, treatment, follow-up, and prognosis of ARCL1B, we searched the literatures of pubmed and web of science from inception to February 2024 to provide an essential reference for physicians to deepen the understanding of ARCL1B.ConclusionThe EFEMP2 gene mutation identified in this patient has not been previously reported, expanding the mutation spectrum of the gene. This is the first documented case of this disease in the Chinese population. The diagnostic and therapeutic journey of this patient, along with the accompanying literature review, provides valuable insights. It highlights the importance of clinicians maintaining a high level of vigilance when encountering cases involving younger patients with multiple pulmonary artery aneurysms, as they may indicate the presence of this rare disease.